Factors associated with contrast-associated acute kidney injury in an emergency department: A cohort study in Lebanon - Moustafa Al Hariri; Sally Al Hassan; Malak Khalifeh; Hani Tamim; Imad El Majzoub; Tharwat El Zahran (PLoS ONE, 2025)
Background Contrast-associated acute kidney injury (CA-AKI) is a common problem in hospitals, particularly in low-middle-income countries (LMIC), due to limited resources and a high prevalence of comorbidities. Kidney function evaluation using serum creatinine levels before contrast administration leads to increased length of stay and delayed patient care. This study aimed to identify factors associated with CA-AKI in emergency department (ED) patients in an LMIC. Identifying these factors is essential for enhancing patient care and guiding clinical practice by allowing for the early detection and management of patients at risk. Methods This study is a retrospective cohort study conducted at the largest tertiary care center’s ED in Lebanon between November 2018 and December 2019. The study included ED patients who underwent computed-tomography (CT) with contrast. Bivariate and logistic regression analyses were performed to compare the characteristics of patients who developed AKI with those who did not by using SPSS package. The Institutional Review Board (IRB) at the American University of Beirut (AUB) approved this study under protocol ID BIO-2020-0276, which was performed per the Declaration of Helsinki. The IRB waived the need to consent patients since many of them were not followed up at the time of the study. Results The study included 1832 patients, of whom 10.4% (n = 190) developed CA-AKI. Patients aged over 65 had a 1.6-fold higher risk of CA-AKI (aOR = 1.55, 95%CI:1.09-2.2). High blood pressure (≥140 mmHg), high respiratory rate ( ≥ 22), and chronic kidney disease were significantly associated with CA-AKI. The use of loop diuretics (aOR = 2.21, 95%CI:1.49-3.28), beta-lactams (aOR = 4.11, 95%CI:2.63-6.42), and allopurinol (aOR = 2.74, 95%CI:1.43-5.25) were significantly associated with CA-AKI. Conclusions Identifying factors associated with CA-AKI in an emergency setting, such as age, comorbidities, and home medications, can help identify patients at low risk of developing CA-AKI.